Social Media and Tourist Behavior: A Quantitative Study on The Relationship Between Travel Experience Sharing and Travel Intention - Juniawan, I Made; Kusuma Dewi, Luh Gede Leli (West Science Social and Humanities Studies, 2025)
Social media has emerged as a key source of travel information, with content created by users often regarded as more trustworthy than that provided by official tourism organizations. Given that young people make up the majority of social media users, this trend has transformed tourist behavior, where travelers not only visit destinations but also document and share their experiences. Gaining a deeper understanding of this dynamic offers valuable insights for the tourism sector to develop effective marketing strategies and improve interaction with travelers. This research investigates how sharing travel experiences on social media influences the intention to visit a destination, focusing specifically on youth travelers. Using incidental sampling, the study targeted domestic tourists. Through a quantitative method employing regression analysis, five main factors influencing this behavior were identified. The results also demonstrate a positive and significant correlation between travel experience sharing and tourists’ travel intention, with travel experience sharing accounting for 41.7 percent of the variation in travel intention, while the remaining 58.3 percent is attributed to other factors beyond the scope of this study.